ANALISIS PENGETAHUAN KLIEN HIPERTENSI DENGAN PERILAKU PENCEGAHAN KOMPLIKASI HIPERTENSI - Siprianus Abdu (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2018)
Hypertension is a health problem that almost happened in all countries, both the developing and the developed country. Hypertension is a common health problem, if uncontrolled will develop and cause complications. Lack of patient knowledge about hypertension and its complications will impact the increasing incidence and complications of hypertension. This will add to the seriousness of the problems that affect the degree of public health. The purpose of this study is to analyze the relationship between client's knowledge of hypertension with the behavior prevention of complications of hypertension. The population of this study is the hypertensive clients who are hospitalized at the hospital. The samples are 40 respondents with non-probability sampling techniques with incidental sampling approach. This quantitative study includes the observational correlative design with a cross sectional approach which measurement of independent variables and the dependent variable is done simultaneously. Measurement data are processed by using statistical test that is Chi Square (X2) and using SPSS program for Windows version 20. P Value = 0.000 means that the value of p <0.05, which means that there is a relationship between knowledge and behavior of clients with the prevention of complications of hypertension. The results of this study concluded that when the client's knowledge is good, then the behavior of the prevention of complications of hypertension is also good otherwise when the client's knowledge is low then t the behavior of the prevention of complications of hypertension are also low. Knowledge is an important basis for a person to do something good in life.